Immune response in atopic dermatitis: main pathogenetic mechanisms and stage-dependent correlations with age in regard to dermatological and non-dermatological systemic processes - M. B. Drozhdina; E. V. Suslova (Медицинская иммунология)
Atopic dermatitis is one of the most common chronic inflammatory skin diseases caused by both terminal defects in keratinocyte differentiation, and pronounced type 2 immune responses. Atopic dermatitis is a fairly heterogenous disease, depending on the age subtype caused by activation of the Th22, Th17/IL-23 and Th1 cytokine pathway. Clinical studies using classical and targeted therapies have helped to determine contribution of various immune axes to the disease phenotype.We present the modern activation theory mediated by Th2 reactions, due to congenital lymphoid cells of the 2nd group. Correlations between immune response in acute (IL-4, IL-5, IL-13, IL-31, CCL18, IL-22, S100A proteins) and chronic (IFNγ, CXCL9, and CXCL10) manifestations of atopic dermatitis are described. The theory of relationship between clinical manifestations and overexpression of some cytokines (IL-4, IL-13) is discussed. The correlation was shown between peripheral blood phenotype in atopic dermatitis of early childhood and in adult patients and individual production of serum biomarkers. In addition to excess Th17 production, early onset of atopic dermatitis in children correlated with elevated levels of antimicrobial peptides, which may serve as a signaling marker that triggers the disease. The article provides information about relationship between atopic dermatitis and other systemic non-allergic processes and diseases (psoriasis, atherosclerosis, cardiovascular diseases, obesity). Despite different polarity of T cells in atopic dermatitis and psoriasis, and different groups of cytokines produced in these diseases. Psoriasis is most of all due to Th17 associated with activation of IL-17, whereas atopic dermatitis is a consequence of Th2 dominance and associated excessive production of IL-4 and IL-13. The both diseases show activation of Th1 and Th22 with increased production of interferon-γ and IL-22, respectively. The article also concerns an interesting hypothesis on effects of the TWEAK protein upon clinical course of atopic dermatitis and psoriasis. In response to increased TWEAK activity, keratinocytes and skin fibroblasts produce a number of chemoattractant and pro-inflammatory factors commonly found in atopic dermatitis and psoriasis, in particular IL-13 and IL-17. TWEAK is not a single etiological factor for atopic dermatitis or psoriasis, but it causes the production of chemokines that promote chemotaxis of pathogenic inflammatory cells into the skin. With further studies of this pathogenetic factor, it will be possible to synthesize a new targeted drug for the treatment of atopic dermatitis and psoriasis.